Spatial distribution and challenges in European Union funding: A perspective from tourism projects - Isabel Torres; María-Dolores Teruel-Serrano; María José Vi\~nals (Annals of Tourism Research Empirical Insights, 2025)
Tourism is a key economic sector, yet its prominence within European Union funding remains limited. This paper presents the first multi-programme estimate of tourism-related EU funding between 2007 and 2020, covering eleven major programmes. An estimated exteuro5.45 billion-2.23~% of total EU funding-was allocated, primarily through regional and structural funds. Support from other instruments was marginal, despite tourism's multisectoral relevance. The findings reveal spatial disparities linked to institutional capacity and governance structures, reflecting broader challenges associated with project-based funding. This study contributes to ongoing policy debates around the future Multiannual Financial Framework (2028-2034) and the EU Sustainable Tourism Strategy, calling for more coherent and inclusive support for tourism across Member States.
Keywords: 330; EU funding; European Union; Territorial distribution; Tourism; Tourism policy